International Finance and Income Convergence : Europe is Different - Leigh, Daniel (IMF Working Papers; Working Paper ;, 2007)
Recent studies conclude that the ongoing global financial integration may have had little or no value in advancing economic growth, especially in poor countries. Capital is often found to flow "uphill" from poor to rich countries. And, when it does flow into the less developed economies, it is negatively correlated with growth, calling into question the desirability of foreign capital. In this paper we report that Europe-including the new member states of the European Union-provides a counterexample to these global anomalies. With increasing financial integration, capital in Europe has traveled "downhill" from rich to poor countries, and has done so with gathering strength. These inflows have been associated with significant acceleration of income convergence.